KEMANDIRIAN DENGAN KUALITAS HIDUP LANSIA - Lamere, Frany; Geneo, Martinus; Oroh, Cindi (Fakultas Keperawatan, Universitas Katolik De La Salle Manado, 2023)
Background: The quality of life of the elderly is a complex component which includes life expectancy, satisfaction with life in terms of health, physical and mental, cognitive function, income, living conditions, social support and social networks in daily life. When there are limitations in fulfilling the needs independently of the elderly, the quality of life of the elderly will decrease. Objective: To determine the relationship between elderly independence and the quality of life of elderly people in South Koha Village. Method: This research is quantitative research with a correlation research design. The research was carried out in South Koha Village. Village. The population is all elderly people who live in South Koha Village and sampling used a total sampling of n = 101 respondents. The instruments used are the Barthel Index and Older People Quality of Life (OPQOL-Brief). Results: Based on the results of the Spearman's rho test analysis, it was found that p value = 0.000 < 0.05. Conclusion: There is a significant relationship between independence in carrying out activities and the quality of life of elderly people in South Koha Village. Therefore, it is important to be able to modify everything that can help elderly people to be able to meet their needs independently.